Histopathological assessment of Atlantic salmon exposed to calcium oxide particles: a controlled clinical study - Ciani, Elia; Lie, Kai-Inge; Stormoen, Marit; Antonsen, Stein Ivar; Jørgensen, Even Hjalmar (Frontiers in Aquaculture, 2024)
Particulate calcium oxide (CaO) has been successfully used for the control of sea urchin and starfish populations. Recent studies have proven its efficacy to kill planktonic copepods, making it a promising and cheap candidate for salmon louse control in Atlantic salmon (Salmo salar) farming industry. Additionally, preliminary laboratory test demonstrated that exposure to 0.2-0.6 g/L fine CaO particles induced significant mortality in salmon louse (Lepeophtheirus salmonis) planktonic stages. The present study investigated the effects of water treatment with fine CaO particles [0.2 g/L (127.4 g/m 2 ); 0.1-0.3 mm], conducted twice a week for three consecutive weeks at 5˚C and 12˚C, on Atlantic salmon post-smolt in a flow-through system. The study compared mortality rates and histopathology of skin, eyes, gills, and intestine between treated and untreated, control salmon. The results indicated that CaO exposure did not induce fish mortality nor histopathological damages in skin, eyes, or intestine. While there was no significant effects of CaO exposure on gills inflammation or hyperplasia, the exposure did increase the occurrence of gills vascular injuries and necrosis in small portions of tissue (<10% of the respiratory gill tissue in most of the samples) by 60% and 35% respectively. The effect was not modulated by temperature or time.